Pengukuran Parameter Sifat Viskoelastis Biji Kedelai Berdasarkan Model SMK (Simplified Maxwell-kelvin) dan DM (Degenerated Maxwell) - I.K.Tastra . (PERTETA, 2008)
Soybean seed with high proportion (25%) ofhard grain is reported to have long storability and minimum pre harvest deterioration. Therefore, it is imperative to measure the parameter ofthe viscous-elastic properties of soybean grain in conjunction with the hard grain characteristic. This information is important in optimizing the post harvest processing system of soybean seed, especially at threshing process. Wi/is variety of soybean with grain moisture of 13.78 % wet basis was used in this study. The measurement ofthe parameters of the soybean grain viscous-elastic property was conducted using a Rheometer (Model EZteslCE, Merek Shimadzu), based on the SMK and OM models, combining three parameters of spring ( K. ) and dashpot ( C. ). The measurement of the parameters of the soybean grain viscous-elastic property was done with 15 replications through 15 soybean grains taken randomly. The values of soybean grain viscous-elastic parameters using SMK model were K1 = 48.21 N/mm (Standard Deviation (SO) = 3.46 N/mm) K2 = 45.44 N/mm (SO =8.66 N/mm) and C1 = 380.79 N-s/mm (SO =59.19 N-s/mm) respectively. While using OM Model the values ofsoybean grain parameters were K3 = 23,34 N/mm (SO = 3,46 N/mm); K4 =24.87 N/mm (SO =1.68 N/mm) and C2 = 1001.03 N-s/mm (SO =7.70 N-s/mm) respectively. Model validation show that both SMK and OM models had coefficient determination (R2) > 0.98. Keywords: Soybean grain, Viscous-elastic property, SMK and OM models. Diterima: 28 Juni 2007; Disetujui: 13 Oktober 2007